Imāmah dalam Islam: Kajian Historis dan Relevansinya terhadap Kepemimpinan Kontemporer - Akhmad Hafi; Noormala Santi; Akhmad Zaki Yamani (PT. Pustaka Andil Lestari, 2025)
The concept of imamah in Islam plays a vital role in discussions of leadership, both in religious and political contexts. Following the death of the Prophet Muhammad (PBUH), the Muslim community faced the fundamental question of who should lead and how leadership should be exercised. Diverging views between Sunni and Shia schools of thought on imamah have produced various theological and historical interpretations. This article aims to examine the historical development of the concept of imamah in Islam and to explore the relevance of its core values to contemporary models of leadership. The study employs a qualitative approach using literature review methods, analyzing both primary classical sources and contemporary academic works. The findings reveal that, although imamah emerged in a different sociopolitical context, its foundational values—such as justice, knowledge, and moral responsibility—remain relevant in shaping ethical and integrity-based leadership today. It concludes that imamah is not merely a historical concept but can serve as a source of inspiration for modern leadership rooted in Islamic principles.